A novel pathogenic SLC12A5 missense variant in epilepsy of infancy with migrating focal seizures causes impaired KCC2 chloride extrusion - Viivi Järvelä; Viivi Järvelä; Viivi Järvelä; Mira Hamze; Jonna Komulainen-Ebrahim; Jonna Komulainen-Ebrahim; Jonna Komulainen-Ebrahim; Elisa Rahikkala; Elisa Rahikkala; Elisa Rahikkala; Johanna Piispala; Mika Kallio; et al. (Frontiers in Molecular Neuroscience, 2024)
The potassium-chloride co-transporter 2, KCC2, is a neuron-specific ion transporter that plays a multifunctional role in neuronal development. In mature neurons, KCC2 maintains a low enough intracellular chloride concentration essential for inhibitory neurotransmission. During recent years, pathogenic variants in the KCC2 encoding gene SLC12A5 affecting the functionality or expression of the transporter protein have been described in several patients with epilepsy of infancy with migrating focal seizures (EIMFS), a devastating early-onset developmental and epileptic encephalopathy. In this study, we identified a novel recessively inherited SLC12A5 c.692G>A, p. (R231H) variant in a patient diagnosed with severe and drug-resistant EIMFS and profound intellectual disability. The functionality of the variant was assessed in vitro by means of gramicidin-perforated patch-clamp experiments and ammonium flux assay, both of which indicated a significant reduction in chloride extrusion. Based on surface immunolabeling, the variant showed a reduction in membrane expression. These findings implicate pathogenicity of the SLC12A5 variant that leads to impaired inhibitory neurotransmission, increasing probability for hyperexcitability and epileptogenesis.